Using Monty Python and The Holy Grail to Teach the van Hiele Model for Geometric Thought and Logic - Moyer, Todd O (Ohio Journal of School Mathematics, 2018)
One of the greatest comedy movies of all time is Monty Python and The Holy Grail. The author presents an activity to engage preservice teachers in the van Hiele Model for Geometric Thought and logic using specific clips from the movie. The author provides questions that complement the clips.